Definition of a goal elicitation process - Thomas, Pablo Javier (2005)
Requirement Engineering plays an essential role at the initial stage in the software development life cycle. This discipline entails three processes: Requirements Elicitation, Specification and Validation. Elicitation has, as a primary goal, the knowledge acquisition over a problem domain. In order to do this, different techniques are applied according to the kind of information to be elicited and the time and resources available for the analyst. One of the most important techniques is Goal Analysis. It was established, once analysed the most important approaches as far as use is concerned (GBRAM, KAOS, Softgoals, Ideas, Rolland, Loucopoulos) that those approaches lack a Goal Elicitation Process, in other words, they lack a methodology that shows clearly what are to be made to obtain Goals. This Thesis proposes a process to elicit Goals based on Annie Antón's approach (GBRAM) from Scenarios applying the schema proposed by Julio Leite. To do this 12 rules were defined which, applied to Scenario elements, allow us to obtain the goal elements with GBRAM schema.